Application of Recombination -Induced Tag Exchange (RITE) to study histone dynamics in human cells - Thom M. Molenaar; Marc Pagès-Gallego; Vanessa Meyn; Fred van Leeuwen (Epigenetics, 2020)
In eukaryotes, nucleosomes form a barrier to DNA templated reactions and must be dynamically disrupted to provide access to the genome. During nucleosome (re)assembly, histones can be replaced by new histones, erasing post-translational modifications. Measuring histone turnover in mammalian cells has mostly relied on inducible overexpression of histones, which may influence and distort natural histone deposition rates. We have previously used recombination-induced tag exchange (RITE) to study histone dynamics in budding yeast. RITE is a method to follow protein turnover by genetic switching of epitope tags using Cre recombinase and does not rely on inducible overexpression. Here, we applied RITE to study the dynamics of the replication-independent histone variant H3.3 in human cells. Epitope tag-switching could be readily detected upon induction of Cre-recombinase, enabling the monitoring old and new H3.3 in the same pool of cells. However, the rate of tag-switching was lower than in yeast cells. Analysis of histone H3.3 incorporation by chromatin immunoprecipitation did not recapitulate previously reported aspects of H3.3 dynamics such as high turnover rates in active promoters and enhancers. We hypothesize that asynchronous Cre-mediated DNA recombination in the cell population leads to a low time resolution of the H3.3-RITE system in human cells. We conclude that RITE enables the detection of old and new proteins in human cells and that the time-scale of tag-switching prevents the capture of high turnover events in a population of cells. Instead, RITE might be more suited for tracking long-lived histone proteins in human cells.